1989
DOI: 10.1128/mcb.9.11.4807
|View full text |Cite
|
Sign up to set email alerts
|

The ras-like protein p25rab3A is partially cytosolic and is expressed only in neural tissue.

Abstract: An antipeptide antiserum has been developed against a sequence near the C terminus of the small guanmne nucleotide-binding protein p25F*A. This protein is the product of one of a large number of genes that show homology to the ras proto-oncogenes. Immunoblotting with the antiserum specifically detected a 25-kilodalton protein in brain membranes. This protein coeluted from a MonoQ high-resolution ion-exchange column with a 25-kilodalton GTP-binding protein at a salt concentration similar to that known to elute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Effector domain peptides have, in fact, been shown to inhibit transport in the biosynthetic pathway (Plutner et al, 1990). Proteins have been identified that can escort rab proteins in the cytosol (GDI), stimulate GTP hydrolysis or facilitate GDP/GTP exchange (Huang et al, 1990;Sasaki et al, 1990;West et al, 1990;Burstein et al, 1991;Tan et al, 1991;Burstein and Macara, 1992). Other proteins, which include putative components of the transport machinery, are expected to interact with rab proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Effector domain peptides have, in fact, been shown to inhibit transport in the biosynthetic pathway (Plutner et al, 1990). Proteins have been identified that can escort rab proteins in the cytosol (GDI), stimulate GTP hydrolysis or facilitate GDP/GTP exchange (Huang et al, 1990;Sasaki et al, 1990;West et al, 1990;Burstein et al, 1991;Tan et al, 1991;Burstein and Macara, 1992). Other proteins, which include putative components of the transport machinery, are expected to interact with rab proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, rab proteins could also be involved in intracellular traffic. With the exception of rab3p, which seems to be only present in nervous and endocrine cells (7)(8)(9)(10)(11)(12), rab lAp, 2p, 4p, 5p, and 6p appear to be ubiquitously distributed (6,7). Mature phagocytes are involved in different functions such as degranulation, phagolysosome formation, and directed locomotion that require organized intracellular traffic and sorting of granules and vesicles (1 3, 14).…”
Section: Introductionmentioning
confidence: 99%
“…Rab3A GTPase is expressed predominantly in neuronal and chromaffin cells, where it is associated with the membranes of synaptic vesicles and chromaffin granules (8,13,25,31). Membrane attachment requires the posttranslational modification of the two C-terminal Cys residues of Rab3A by geranylgeranylation (15).…”
mentioning
confidence: 99%